Development of a Dashboard-Based Information System to Improve Prospective Customer Engagement at PLN UP3 Bima - Aldillah; Zumhur Alamin; Sutriawan; Teguh Ansyor Lorosae; Fitriani Ramadhani; Lailia Rahmawati (Indonesian Applied Research Computing and Informatics, 2025)
PT PLN (Persero) UP3 Bima faces challenges in effectively managing and analyzing prospective customer data, resulting in delays in decision-making and suboptimal utilization of potential connected power. This study aims to develop an interactive dashboard system using Looker Studio and Google Sheets to improve operational efficiency and support digital transformation within PLN. The methodology includes user needs analysis, real-time data integration from Google Sheets, and the design of data visualizations in Looker Studio based on key parameters such as customer growth trends, sector classification, and potential connected power. The implementation results show that the system effectively delivers accurate and timely information, assisting management in identifying opportunities to increase new customer connections. The impact of this system includes enhanced effectiveness in managing prospective customer data, faster decision-making processes, and stronger support for data-driven strategies to increase customer acquisition in a measurable way.